Особенности применения четырехзондового индукционного каротажа в тонкослоистых разрезах Днепровско-Донецкой впадины - Миронцов, Н.Л. (Геоінформатика, 2017)
Создан и численно реализован алгоритм решения обратной задачи низкочастотного индукционного каротажа для определения геоэлектрических параметров тонкослоистых разрезов типа “рябчик”. Решение основано на возможности введения поправок “за скважину”, “за скин-эффект” и “за вмещающие породы”. Проведено экспериментальное тестирование созданного алгоритма в условиях Днепровско-Донецкой впадины. На примере реального скважинного материала показано, что четырехзондовый индукционный каротаж позволяет уверенно исследовать тонкослоистые разрезы типа “рябчик”. При этом вертикальное разрешение метода оказывается сопоставимым или выше, чем у вспомогательных методов, а в некоторых случаях индукционный каротаж — единственный метод, который позволяет уверенно исследовать продуктивные пласты. Створено та реалізовано у числовому вигляді алгоритм розв’язання оберненої задачі низькочастотного каротажу для визначення геоелектричних параметрів тонкошаруватого розрізу типу “рябчик”. Розв’язання ґрунтується на можливості введення поправок “за свердловину”, “за скін-эфект” і “за вмісні породи”. Проведено експериментальне тестування створеного алгоритму в умовах Дніпровсько-Донецької западини. На прикладі реального свердловинного матеріалу показано, що чотиризондовий індукційний каротаж дає змогу впевнено досліджувати тонкошаруваті розрізи типу “рябчик”. При цьому вертикальна роздільна здатність методу виявляється зіставною чи вищою, ніж у допоміжних методів, а в деяких випадках індукційний каротаж є єдиним методом, за допомогою якого можна впевнено досліджувати продуктивні пласти. Purpose The purpose of the article is to create and numerically implement an algorithm for solving the inverse problem of low-frequency induction logging for oil and gas in order to determine the geoelectrical parameters of thin-layered cuts of the “grouse” type; to perform experimental testing of the created algorithm in the Dnieper-Donets Basin conditions. Design/ methodology/ approach In order to create the algorithm for solving the inverse problem, we used corrections “for the well”, “for the skin-effect” and “for the surrounding rocks”. The correction “for the surrounding rocks” was used in the numerical solution of the unstable inverse problem of induction low-frequency logging. Findings Based on the example of the real borehole material, the study showed that the four-probe induction logging allows us to reliably study thin-layered cuts of the “grouse” type in the Dnieper-Donets Basin. At the same time, the vertical resolution of the method proves to be comparable or higher than that of the auxiliary methods, and in some cases induction logging is the only method that distinguishes productive beds. Practical value/ implications The dismemberment of thin-layered cuts of the “grouse” type with simultaneous precise determination of the geoelectrical parameters of each interlayer will permit to increase the daily flow rate of the useful well fluid in the Dnieper-Donets Basin conditions.